The Effectiveness of Correctional Institutions for Children, Female, and Elderly Inmates in Sidoarjo District - Sri Warjiyati; Imron Rosyadi; Zeti Nofita Sari; Fariza MD Sham (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
Correctional Institutions are institutions implementing the criminal system whose function is to develop correctional inmates, including, in this case, women who are serving sentences and required to participate in the entire series of training activities in correctional institutions. In this case, the effectiveness of coaching prisoners can provide a good role model for others, especially prisoners of female, children, and the elderly. Then, the supporting factors can be used as examples to become even better in the future, and better solutions can be found for factors that can hinder development. This research aims to determine the pattern of coaching females, children, and elderly prisoners and to determine the factors that inhibit and support coaching. Synergy is needed between all parties involved, starting from prisoners, correctional officers, and related agencies, in cooperating with each other in carrying out training for female, child, and elderly prisoners to overcome problems in the implementation of training for female, child, and elderly prisoners, For this reason, it is necessary to carry out treatment and guidance to achieve better goals, and if the convict leaves, he will create an independent character and have a better leadership spirit.